2011
DOI: 10.1177/0309324711428836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and strain rate on the dynamic responses of three polymer-bonded explosives

Abstract: Polymer-bonded explosives (PBXs) are typical particulate composites of energetic crystals in a polymer matrix, which have a volume fraction of 60% to 95%. They are engineered to provide reliable performance and maximum safety envelopes through reduction of their sensitivity. There are three kinds of polymer-bonded explosive materials; namely, PBX1, PBX2, and PBX3. The last two polymer-bonded explosives were recently invented, in search of the more insensitive polymer-bonded explosive but with high detonation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…11 Li et al investigated the uniaxial compressive stress-strain behavior of three PBXs and found that the yield strength of PBXs is negatively correlated with temperature and positively correlated with strain rate. 12,13 The compressive and tensile properties of PBX9501 and 9502 have been investigated over broad temperature ranges and drastically different loading strain rates. 14 The dynamic response of an aluminized PBX over a temperature range of À55 C to À2 C and under a xed loading strain rate has been tested using the split Hopkinson pressure bar (SHPB).…”
Section: Introductionmentioning
confidence: 99%
“…11 Li et al investigated the uniaxial compressive stress-strain behavior of three PBXs and found that the yield strength of PBXs is negatively correlated with temperature and positively correlated with strain rate. 12,13 The compressive and tensile properties of PBX9501 and 9502 have been investigated over broad temperature ranges and drastically different loading strain rates. 14 The dynamic response of an aluminized PBX over a temperature range of À55 C to À2 C and under a xed loading strain rate has been tested using the split Hopkinson pressure bar (SHPB).…”
Section: Introductionmentioning
confidence: 99%
“…Some research works on dynamic mechanical properties of PBXs have been done [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The dynamic and static mechanical properties of PBXs were very different [5].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic and static mechanical properties of PBXs were very different [5]. Furthermore, researchers have paid more attention to the effect of temperature on dynamic mechanical response of PBXs [6][7][8][9][10][11][12][13][14][15][16]. The stress-strain responses of PBX9501 and mock 9501 were tested under different temperatures and strain rates [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present elastic-viscoplastic collapse models are mostly based on the ductile mechanical property based on Carroll-Holt's model [14]. On the contrary, many experimental results show that explosives, such as PBXs, have typical brittle mechanical properties under impact loading [15][16][17]. The initial defects or damage in the explosives is inevitable in the process of production or usage.…”
Section: Introductionmentioning
confidence: 99%